Corneal sequestra in cats: 175 eyes from 172 cases (2000–2016). (29th January 2021) - Multari, D.; Perazzi, A.; Contiero, B.; Carobbi, B.; Bertoldi, M.; Iacopetti, I.
Abstract : Objectives: To report the clinical outcomes of different surgical treatments used to manage feline corneal sequestra in a large number of cases. Materials and Methods: Medical records of 172 cats affected by feline corneal sequestra and surgically managed by different techniques were retrospectively evaluated. Signalment, surgical technique, visual outcomes, postoperative corneal clarity and recurrence were evaluated. Results: One hundred and seventy‐two cats (175 eyes) of different breeds, ages and sex were included in the retrospective case series. The Persian was the most represented breed (123/172; 71.5%), followed by Exotic Shorthair breed (21/172; 12.2%), Domestic shorthair breed (21/172; 12.2%) and a smaller group of other different breeds (7/172). Surgical management included a superficial (84/175 eyes) or deep (91/175 eyes) lamellar keratectomy in association with the following covering techniques (tectonic support and/or protective support): nictitans membrane flap (n=84), conjunctival pedicle graft (n=52), BioSISt graft (n=9), corneoconjunctival transposition (n=7), corneoconjunctival transposition+nictitans membrane flap (n=6), conjunctival free island graft (n=6), BioSISt+conjunctival pedicle graft (n=6), BioSISt+nictitans membrane flap (n=4) and bridge conjunctival graft (n=1). At the end of the retrospective case series, visus was present in all patients and no or mild corneal opacity was detected in 86% (151/175 eyes) of the patients. Sequestra recurred in 20 eyes (20/175; 11.4%) within 2 years. Clinical Significance: This paper describes the clinical outcomes of a large number of cases of feline corneal sequestra treated with varying surgical techniques and provides useful insight regarding the prognosis and outcomes of these techniques within feline ophthalmology.